The Mediating Role of Distress Tolerance in the Relationship Between Childhood Maltreatment and Mental Health Outcomes Among University Students. Issue 15 (August 2021) - Robinson, Martin; Ross, Jana; Fletcher, Shelley; Burns, Carol Rhonda; Lagdon, Susan; Armour, Cherie
A wealth of empirical literature has documented that the experience of childhood maltreatment is related to an increased risk for the development of psychopathologies in adulthood. Empirical studies examining the factors that could possibly explain this relationship, however, remain sparse. The emerging literature on distress tolerance (DT) suggests that it could possibly act as an explanatory or mediating factor within this relationship. The current study, therefore, examined the mediating role of DT in the relationship between childhood maltreatment and psychopathology (posttraumatic stress disorder, depression, anxiety, and alcohol use) in adulthood in a university student population sample ( N = 642). Results showed that childhood maltreatment was positively associated with caseness for all mental health outcomes under investigation. It was also found that individuals with higher levels of DT were less likely to experience adverse mental health outcomes. The results of the mediation analysis indicated that the exposure to childhood maltreatment remained associated with elevated risk for being in the symptomatic group across mental health outcomes, and that DT significantly mediated this relationship. These results provide insight into the relationship between childhood maltreatment and mental ill-health later in life, highlighting the importance of considering DT as a potential risk and resilience factor in this relationship.